Penerapan VSM dan WAM dalam Meningkatkan Efisiensi Operasional Produksi di CV Tahu Bandung NN - Saputri, Zaniar Aisyah; Hartini, Sri; Pradipto, Masri; Novitasari, Tri (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The objective of this research was to identify the most dominant waste, calculate the average cycle time per unit at each work station, and provide suggestions for improving the production process. The approach used was Lean Manufacturing with the tools of Value Stream Mapping (VSM) and Waste Assessment Model (WAM). VSM was used to map the process flow and identify non-value-added activities, while WAM was used to assess the dominance of waste using the Waste Relationship Matrix (WRM) and Waste Assessment Questionnaire (WAQ). The analysis results showed that defects were the most significant waste, contributing 14.57%. The main causes were inconsistencies in boiling temperatures and printing errors. In addition, imbalances in cycle times between work stations were found. Proposed improvements focused on the Future State VSM, in the form of process standardization, temperature control, and rearrangement of work areas. The implementation of this method is expected to improve production efficiency sustainably.